The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/adfm.201803969
|View full text |Cite
|
Sign up to set email alerts
|

Functional Peptide Nanofibers with Unique Tumor Targeting and Enzyme‐Induced Local Retention Properties

Abstract: An effective tumoral delivery system should show minimal removal by the reticuloendothelial system (RES), promote tumor uptake and penetration, and minimize on-site clearance. This study reports the design and synthesis of advanced self-assembling peptide nanofiber precursor (NFP) analogues. The peptidic nature of NFP offers the design flexibility for on-demand customization with imaging agents and surface charges while maintaining a set size, allowing for real-time monitoring of kinetic and dynamic tumoral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 82 publications
1
42
0
Order By: Relevance
“…[55][56][57] Lipopeptides containing a sequence of positively-charged aminoacid residues and an anchored fatty acid tail tend to self-assemble into a variety of nanostructures such as nanotubes, nanorods, nanofibrils, nanotapes, nanospheres, etc. [58][59][60][61][62] Modifying the amino-acid sequence and extending the hydrogen bonding, hydrophobic, electrostatic, π-π interactions, and van der Waals interactions can affect the shapes of the formed nano-assemblies, [63][64][65] their tendency to form three-dimensional networks, and their interactions with the biological membranes. 66,67 Studies have indicated that the self-assembly state (monomer, dimer, oligomer…) and the nanoarchitecture type may influence the biological outcome of the peptide amphiphiles in in vitro and in vivo applications.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] Lipopeptides containing a sequence of positively-charged aminoacid residues and an anchored fatty acid tail tend to self-assemble into a variety of nanostructures such as nanotubes, nanorods, nanofibrils, nanotapes, nanospheres, etc. [58][59][60][61][62] Modifying the amino-acid sequence and extending the hydrogen bonding, hydrophobic, electrostatic, π-π interactions, and van der Waals interactions can affect the shapes of the formed nano-assemblies, [63][64][65] their tendency to form three-dimensional networks, and their interactions with the biological membranes. 66,67 Studies have indicated that the self-assembly state (monomer, dimer, oligomer…) and the nanoarchitecture type may influence the biological outcome of the peptide amphiphiles in in vitro and in vivo applications.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the optimal drug ratio offering the strongest synergistic effect on the spheroids was 1:30. Further studies are required to investigate whether the observed discrepancies originated from differences in spheroidal penetration, and thus cellular uptakes, of the 2 drugs [40,41]. Overall, we demonstrated that our drug combination synergism was volatile, and strongly relied on the applied drug ratio as well as the employed cell culture and tumor spheroid models.…”
Section: Sal and Das Synergistically Inhibited Different Bc Cell Linementioning
confidence: 84%
“…These results suggest that peptidic nanofibers through noncovalent strategies have a remarkable potential for DNA delivery. Obviously, PNFs lend themselves to theranostic applications and have been widely employed as advanced materials for imaging [78]. Accordingly, gold nanoclusters (AuNCs) were introduced into self-assembled PNFs to enhance their luminescence efficiency.…”
Section: Nanofibersmentioning
confidence: 99%